A Study of Regulatory Challenges of Pediatric Oncology Phase I/II Trial Submissions and Guidance on Protocol Development. Issue 4 (12th July 2021) - Beck, Lydia; Witt, Ruth; Nesper‐Brock, Martina; Milde, Till; Hettmer, Simone; Frühwald, Michael C.; Rössig, Claudia; Fischer, Matthias; Reinhardt, Dirk; Taylor, Lenka A.; Riedel, Claudia; Witt, Olaf; et al.
Abstract : The purpose of this study was to identify key deficiencies in pediatric oncology early phase clinical trial protocols in Germany and to provide guidance for efficient trial protocol development. A systematic review of the response letters of German competent authorities (CAs) and Ethics Committees to phase I/II pediatric oncology trial submissions in the period from 2014 to 2019 was performed. Documents were requested from all five Society for Paediatric Oncology and Haematology in Germany (GPOH) phase I/II trial networks plus all nine German Innovative Therapies for Children with Consortium Cancer (ITCC) centers. A blinded dataset containing aggregated data from 33 studies was analyzed for validation. All deficiencies were reviewed, listed, and weighted using a structured matrix according to frequency, category, significance, and feasibility. In total, documents of 17 trials from 6 different sites were collected. Two hundred fifty deficiencies identified by the CAs were identified and categorized into eight categories. "Toxicity and safety" was the most prominent category (27.6%), followed by "Manufacturing and Import" (18%). The majority of deficiencies were categorized as minor and potential measures as easy to address, but an important group of major and difficult to implement deficiencies was also identified. The blinded validation dataset confirmed these findings. The majority of the EC deficiencies could be resolved by changing the wording in the patient‐facing documents. In conclusion, this study was able to detect a pattern of key deficiencies. Most of the shortcomings can be anticipated by minor changes in the protocol and increased awareness can prevent time‐consuming revisions, withdrawals, or even rejections. A corresponding guideline describing key regulatory aspects is provided.